Evaluating the role of high-sensitivity C-reactive protein in asthmatic Iraqi patients and its correlation with parameters of patients’ clinical characteristics and pulmonary function tests - Najdat, Muhammed Saleh; Lutfi, Ahmed M (Asian Journal of Medical Sciences, 2016)
Aims and Objectives: To evaluate the relevance of high-sensitivity assays for C-reactive protein (hs-CRP), as a sensitive marker of inflammation in asthmatic Iraqi patients. Additionally, correlations of serum levels of hs-CRP with patients’ clinical characteristics and pulmonary function tests (PFTs) will be studied in a cross-sectional design. Materials and Methods: A random sample of 58 individuals were divided into a healthy (control) group (n = 12) and two groups of adult patients with chronic stable asthma; (n = 22) patients had been receiving inhaled corticosteroids (inhaled corticosteroid-positive, or ICS+VE, group) for the past 2–3 months, and (n = 24) steroid-naive patients (inhaled corticosteroid-negative, or ICS-VE, group). The selected individuals were subjected to hs-CRP measurement and PFTs. Results: The forced expiratory volume in one second (FEV1)/forced vital capacity (FVC), was measured in all subjects. In the ICS+VE and the ICS-VE groups, there was a significant correlation between the level of hs-CRP and FEV1/FVC with r: ?0.891 and a p-value of < 0.0005 for both groups. In the ICS-VE group, 78.5% had significant clinical symptoms, whereas only 22.7% of the ICS+VE group had significant clinical symptoms. This difference (for the prevalence of clinical symptoms) was significant with a chi-square value of 19.59, degree of freedom (df) = 1, and p < 0.0005. Conclusion: In the ICS-VE group, the level of hs-CRP was significantly higher than in both the ICS+VE group and the control group. The values of the PFTs were significantly lower in the ICS-VE group. The prevalence of clinical features was significantly higher in the ICS-VE group. Asian Journal of Medical Sciences Vol. 7(3) 2016 47-53